Addition of conjugated linoleic acid in whole milk improves lipid profile in high fat diet induced hypercholesterolemia of rats - Arta Farmawati; Rio Jati Kusuma; Bayu Sigha Iswara; . Wulandari; Kurniati Dwi Utami; Istiti Kandarina (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Conjugated linoleic acid (CLA) is an isomer of linoleic acid that has been shown to havemany beneficial effects in prevention of atherosclerosis, hypertension, cardiovasculardiseases and improve immune function. Although majority of CLA in the diet are derivedfrom dairy product such as milk, however, the content of CLA in milk is affected by cow’sdiet. The aim of this study was to investigate the beneficial effect of CLA supplementationin milk for improving lipid profile in high fat diet of rats. Twenty four male Sprague Dawleyrats aged 8 weeks were given high fat diet for 3 weeks to induce hypercholesterolemia.Six rats were maintained in standard diet as control. Rats then were divided into 4 groupsi.e. normal control, negative control, high fat diet+CLA 0.5%, high fat diet + CLA 0.5%supplemented skim milk, and high fat diet + CLA 0.5% supplemented whole milk. Bloodsample was drawn after high fat diet induced hypercholesterolemia and after 4 weeksof treatment for total cholesterol, triglyceride, low-density lipoprotein cholesterol (LDLcholesterol), and high density lipoprotein cholesterol (HDL cholesterol) analysis. Bodyweight was measured each week. Results showed that body weight was significantlyincrease in all groups received high fat diet (p<0.05). There was no significant differencein body weight between treatment group (p>0.05). Total cholesterol, triglyceride, andLDL cholesterol was significantly decrease in whole milk followed by significant increasein HDL cholesterol level. Skim milk supplemented with CLA had only modest effect ontriglyceride and HDL cholesterol level. In conclusion, CLA supplementation in whole milkimproves lipid profile in high fat diet.